Communicable Diseases Intelligence Quarterly Report volume 30 issue 2 June 2006-whole issue - No authors listed (Communicable Diseases Intelligence, 2006)
Contents Annual report of the National Influenza Surveillance Scheme, 2005 Augmentation of influenza surveillance with rapid antigen detection at the point-of-care: results of a pilot study in Tasmania, 2004 Annual report of the Australian Gonococcal Surveillance Programme, 2005 Annual report of the Australian Meningococcal Surveillance Programme, 2005 Multi-drug resistant Salmonella Java infections acquired from tropical fish aquariums OzFoodNet quarterly report, 1 January to 31 March 2006 Hypovolemic shock and metabolic acidosis in a refugee secondary to O1 serotype Vibrio cholerae enteritis Prevalence and control of trachoma in Australia, 1997-2004 A report from the Communicable Diseases Network Australia: 1 January to 31 March 2006 Letter to the Editor: The limitation of fever case definitions for avian influenza and SARS Communicable Diseases Surveillance: Highlights for 1st quarter, 2006 (gastrointestinal illnesses, sexually transmissible infections, vaccine preventable diseases, vectorborne diseases, other bacterial infections) National Notifiable Diseases Surveillance System tables, 1 January to 31 March 2006 Laboratory Serology and Virology Reporting Scheme tables, 1 January to 31 March 2006 Australian Sentinel Practices Research Network, reporting period 1 January to 31 March 2006 Meningococcal surveillance, reporting period 1 January to 31 March 2006 HIV and AIDS surveillance, reporting period 1 October to 31 December 2005, assessed as at 31 March 2006 Australian childhood immunisation coverage, 1 October to 31 December 2005 cohort, assessed as at 31 March 2006 National Enteric Pathogens Surveillance System, reporting period 1 January to 31 March 2006 Overseas brief, reporting period 1 January to 31 March 2006 (avian influenza, anthrax - inhalation, poliomyelitis, hand foot and mouth disease, mumps virus - genotype G, chikungunya)